Kinetic Study on Pyrolysis of Biomass Components: A Critical Review - Wang, Shurong; Ru, Bin; Lin, Haizhou; Dai, Gongxin; Wang, Yurong; Luo, Zhongyang (Current Organic Chemistry, 2016)
Aiming at promoting the industrial application of biomass pyrolysis technology, many approaches have been explored to reveal pyrolysis reaction mechanism. Among which the thermal analysis kinetics based on mechanism scheme receives significant attention. The kinetic models developed in past decades are classified into five types: one-step global model based on model-fitting method, global model based on model-free method, multi-step successive model, semi-global model and distributed activation energy model. In this review, the computation processes are introduced, and the advantages and disadvantages of these kinetic models are discussed and compared in detail. To obtain a universal kinetic model and simplify the intricate behaviors of biomass pyrolysis, the pyrolytic kinetics of the three major components, namely cellulose, hemicellulose and lignin, have been studied individually. Their pyrolysis behaviors are dramatically different in view of kinetics. It is recommended that the fundamental theory progress which has been made in the solid reaction kinetics should be applied in the biomass pyrolysis kinetics, and a lot of related traditional knowledge in this area needs to be updated urgently.
Keywords: kinetic parameters